Staging of Flood Season for Danjiangkou Reservoir Considering Characteristics of Plum Rain and West China Autumn Rainfall - WANG Xiao-ya, GUO Sheng-lian, WANG Jun, SHI Yi-jun, DONG Fu-qiang, YANG Hai-cong (长江科学院院报)
[Objective] Danjiangkou Reservoir is a core project of the flood control system in the Hanjiang River Basin and a strategic water source for the Middle Route of the South-to-North Water Diversion Project, and its flood season staging schemes directly affect its flood control safety and inter-basin water transfer efficiency. Since its operation, Danjiangkou Reservoir has maintained an annual full storage rate of only 11%. How to improve this rate while ensuring flood safety remains an urgent issue. Existing research on flood season staging mainly focuses on statistical methods, with insufficient attention to the temporal characteristics of typical rainy seasons such as the plum rainy season in the middle-lower Yangtze River and the autumn rainfall in West China. This study aims to provide a theoretical basis and technical support for the operation and management of Danjiangkou Reservoir. [Methods] Based on daily inflow data of Danjiangkou Reservoir from 1961 to 2023, this study conducted preliminary flood season staging analysis using runoff statistical analysis, annual maximum flood analysis, mean change-point analysis, and vector statistical methods. [Results] The results obtained from different methods were relatively consistent. For safety reasons, the flood season was preliminarily divided into three stages. A further comprehensive analysis integrating the temporal patterns of the plum rain and West China autumn rainfall was conducted. The results showed that both exhibited significant temporal and periodic characteristics. From 1951 to 2023, the plum rain in the middle and lower reaches of the Yangtze River began as early as May 25 and ended as late as August 8. From 1961 to 2023, autumn rainfall in West China began as early as August 21 and lasted until November 30. During the plum rain period, when water levels in the middle-lower Hanjiang River were relatively high, any coincidental occurrence between floods from Danjiangkou and downstream floods may trigger flooding in the Hanjiang River Basin. After the plum rainy season ended, the flood control pressure in the middle-lower Hanjiang River decreased, allowing the Danjiangkou Reservoir to gradually release reserved flood control storage capacity. The autumn rainfall in West China started in late August in Sichuan and gradually moved eastward toward the Qinling Mountains, aligning with the autumn flood season. The autumn rainfall in West China directly affected Danjiangkou Reservoir’s storage conditions. During flood events, reservoir regulation must balance flood safety with increasing the full storage rate to fully utilize flood resources. In full consideration of both the plum rain and West China autumn rainfall, the flood season of Danjiangkou Reservoir was ultimately divided into three stages: summer flood season from June 21 to August 10, transition period from August 11 to August 31, and autumn flood season from September 1 to October 10. [Conclusion] Based on meteorological forecasts of end dates of plum rain and West China autumn rainfall, the flood limit water level for the summer flood season can be gradually raised to the level of the autumn flood season. This approach enables early water storage and improves both water resource utilization efficiency and the reservoir’s full storage rate. The research findings provide a theoretical basis for operation and scheduling decisions for Danjiangkou Reservoir.